2021
DOI: 10.1159/000514935
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Statewide Lockdown in Response to COVID-19 Pandemic on Physical Activity Levels of Hemodialysis Patients

Abstract: <b><i>Background/Objectives:</i></b> On March 22, 2020, a statewide stay-at-home order for nonessential tasks was implemented in New York State. We aimed to determine the impact of the lockdown on physical activity levels (PAL) in hemodialysis patients. <b><i>Methods:</i></b> Starting in May 2018, we are conducting an observational study with a 1-year follow-up on PAL in patients from 4 hemodialysis clinics in New York City. Patients active in the study as of Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…In line with the results of our study, many recent studies highlighted a significant increase in physical inactivity in both the general population and in individuals with chronic diseases during lockdown (51). Studies indicated that lockdown measures were associated with significantly reducing physical activity levels in chronic patients like those on hemodialysis (52). Others, like one from the United Kingdom, reported a significant decrease in physical activity during this lockdown in the general population (53).…”
Section: Discussionsupporting
confidence: 91%
“…In line with the results of our study, many recent studies highlighted a significant increase in physical inactivity in both the general population and in individuals with chronic diseases during lockdown (51). Studies indicated that lockdown measures were associated with significantly reducing physical activity levels in chronic patients like those on hemodialysis (52). Others, like one from the United Kingdom, reported a significant decrease in physical activity during this lockdown in the general population (53).…”
Section: Discussionsupporting
confidence: 91%
“… 3 , 8 Although there is widespread interest in intervention delivery modalities, studies evaluating behavior modification incorporating feedback to wearable technology are in their infancy in HD populations. 8 , 9 , 18 In a study of 29 patients receiving HD, Williams et al 19 reported no difference in the number of steps between a feedback group (n = 15) and a control group (n = 14) (5,365 ± 2,765 vs 5,211 ± 2,010, respectively) over 5 weeks.…”
Section: Discussionmentioning
confidence: 98%
“…In their research article Han et al [2] analyzed the impact of lockdown and social distancing measures on physical activity levels of hemodialysis (HD) patients. HD patients are already at an increased risk of reduced physical activity and further limitation could be detrimental.…”
mentioning
confidence: 99%